A wide band low power sub-THz VCO based on CMOS technology - Tang, Zhengci (Nanyang Technological University, 2023)
In this paper, a D band wide tuning range Voltage controlled oscillator (VCO) in TSMC 40 nm CMOS process is presented. Frequency multiplication is achieved by transformer to enter the sub-THz band. The simulated VCO has a frequency tuning range of 140.56GHz to 159.98GHz (12.14%) with a supply voltage of 0.9V. The tuning is realized by DiCAD, switched capacitor array and MOSCAP.